Adsorption of reactive red dye using regenerated activated carbon: batch and column studies - Mohamad Fikri Abas (Penerbit Universiti Malaysia Perlis, 2011)
Reactive azo dyes, such as Reactive Red 120 are commonly use in textile industry. Low utilization degree and its functional group bonds to water is a problem for the removal from wastewater. Granular activated carbon (GAC) used to adsorb reactive dye. It has limited adsorption ability. After some period, the GAC become exhausted and disposed. The exhausted GAC replaced by new GAC for as a result. Regeneration of activated carbon, method to reactivate carbon adsorption capacity using chemical and thermal (pyrolysis) treatment. Purpose on this work is to compare the efficiency of adsorption by activated carbon; fresh, spent, chemical and thermal regeneration towards reactive dye. Batch and column studies were conducted to investigate the performance of the activated carbons. Two equilibrium adsorption isotherm applied; Langmuir and Freundlish. Freundlich adsorption isotherm was found to fit the experimental data from batch testing. Value of R2 for all type of GAC was higher than 0.97, for Freundlish isotherm. Thermal regeneration GAC have higher adsorption capacity, 1.380 mg/g than chemical regeneration GAC, 1.065 mg/g. In fixed bed column modeling, Rapid Small Scale Column Test (RSSCT) used for adsorption of RR120 at three different flow rates was investigated. Flowrate of 5 mL/min was the best flowrate to have longest period time service of activated carbon. Chemical regeneration GAC exhausted at 400 minutes while thermal still in adsorbing process at 400 minutes.